Glabridin Mediate Caspases Activation and Induces Apoptosis through JNK1/2 and p38 MAPK Pathway in Human Promyelocytic Leukemia Cells - Huang, Hsin-Lien (Public Library of Science, 2014)
BACKGROUND: Glabridin, a prenylated isoflavonoid of G. glabra L. roots, has been associated with a wide range of biological properties such as regulation of energy metabolism, estrogenic, neuroprotective, anti-osteoporotic, and skin-whitening in previous studies. However, the effect of glabridin on tumor cells metastasis has not been clearly clarified. Here, the molecular mechanism by which glabridin anticancer effects in human promyelocytic leukemia cells was investigated. METHODOLOGY AND PRINCIPAL FINDINGS: The results showed that glabridin significantly inhibited cell proliferation of four AML cell lines (HL-60, MV4-11, U937, and THP-1). Furthermore, glabridin induced apoptosis of HL-60 cells through caspases-3, -8, and -9 activations and PARP cleavage in dose- and time-dependent manner. Moreover, western blot analysis also showed that glabridin increase phosphorylation of ERK1/2, p38 MAPK and JNK1/2 in dose- and time-dependent manner. Inhibition of p38 MAPK and JNK1/2 by specific inhibitors significantly abolished the glabridin-induced activation of the caspase-3, -8 and -9. CONCLUSION: Taken together, our results suggest that glabridin induced HL-60 cell apoptosis through p38 MAPK and JNK1/2 pathways and could serve as a potential additional chemotherapeutic agent for treating AML.